2016
DOI: 10.1186/s12868-016-0256-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic investigation of regional brain tissue dysfunctions induced by global cerebral ischemia

Abstract: BackgroundTo get a broader view of global ischemia-induced cerebral disorders at the metabolic level, a nuclear magnetic resonance-based metabolomic study was performed to evaluate the metabolic profile changes on regional brain tissues of female and male mice upon bilateral common carotid arteries occlusion (BCCAO) operation.ResultsSignificant metabolic disorders were observed in both cerebral cortex and hippocampus tissues of the experimental mice upon global cerebral ischemic attack. Multiple amino acids we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…In that report, we observed an early upregulation of S1P in CA3 that was not observed in CA1, and we hypothesized that this intracellular S1P upregulation is one of the mechanisms by which the CA3 sub-region evades cell death after tGCI. Previous studies using global cerebral ischemia model have observed several metabolic changes to occur in the hippocampus, such as changes in phosphatidylcholine 31 and other phospholipids 35 as well as small metabolites and amino acids 41 , however, none of these studies attempted an approach as wide-scoped as the one reported here. www.nature.com/scientificreports www.nature.com/scientificreports/ In our work, we highlighted several pathways that were enriched following transient global cerebral ischemia in both CA1 and CA3 sub-regions.…”
Section: Discussionmentioning
confidence: 91%
“…In that report, we observed an early upregulation of S1P in CA3 that was not observed in CA1, and we hypothesized that this intracellular S1P upregulation is one of the mechanisms by which the CA3 sub-region evades cell death after tGCI. Previous studies using global cerebral ischemia model have observed several metabolic changes to occur in the hippocampus, such as changes in phosphatidylcholine 31 and other phospholipids 35 as well as small metabolites and amino acids 41 , however, none of these studies attempted an approach as wide-scoped as the one reported here. www.nature.com/scientificreports www.nature.com/scientificreports/ In our work, we highlighted several pathways that were enriched following transient global cerebral ischemia in both CA1 and CA3 sub-regions.…”
Section: Discussionmentioning
confidence: 91%
“…Cerebral infarction (CI) and ischemia (IS) are common diseases in elderly people seriously affecting the quality of life. Patients with IS exhibit insufficient blood supply, which is considered an early stage of CI ( 1 , 2 ). It is predicted that by 2030, the Chinese population aged ≥60 will be >300 million, and ~2/3 patients with primary cerebral vascular disease will be aged ≥60 years.…”
Section: Introductionmentioning
confidence: 99%
“…The whole pancreatic tissues were quickly removed after the experimental mice were killed by dislocation of the cervical vertebrae, immediately snap-frozen in liquid nitrogen and then stored at −80°C until further analysis. Extractions of polar metabolites from the pancreas tissues were performed following the reported procedure [16][17][18]. In short, tissue samples, which were preweighed and thawed on ice, were homogenized and extracted with an ice-cold methanol-chloroform-water solvent system (4, 4, and 2.85 μL, respectively per mg/tissue).…”
Section: Serum and Pancreas Extraction Proceduresmentioning
confidence: 99%